Identifying potential pitfalls in interpreting mitochondrial DNA mutations of male infertility cases - Palanichamy, Malliya Gounder (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND & OBJECTIVES: Recently, a significantly higher ratio of nucleotide changes in the mtDNA genes: COII, ATPase 6, ATPase 8, ND2, ND3, ND4, and ND5 was reported in spermatozoa from populations of infertile Indian men, compared suggesting that screening for mtDNA mutations could provide insight into the aetiology of male infertility. In this study, we examined the published data and found serious errors in the original acquisition and analysis of the data. METHODS: The mtDNA data associated with male infertility in Indian populations were retrieved from the published sources. The mtDNA substitution values of infertile and control groups were evaluated using phylogenetic methods and previously published mtDNA phylogenies. RESULTS: Most of the mtDNA polymorphisms reported as significantly correlated with infertility were more commonly found in general populations. Further, our analysis showed that some of the mtDNA substitutions were erroneously overestimated in the infertile groups and underestimated in the control groups, and vice-versa. INTERPRETATION & CONCLUSIONS: Contrary to earlier claims, our analysis demonstrated no significant association between the mtDNA polymorphisms and male infertility in these studies. Further, these errors in the published data impune the usefulness of mitochondrial molecular analyses in male infertility diagnosis.